HCT116 colorectal liver metastases exacerbate muscle wasting in a mouse model for the study of colorectal cancer cachexia - Joshua R. Huot; Leah J. Novinger; Fabrizio Pin; Andrea Bonetto (The Company of Biologists, 2020)
Colorectal cancer (CRC) is often accompanied by formation of liver metastases (LM) and skeletal muscle wasting, i.e. cachexia. Despite affecting the majority of CRC patients, cachexia remains underserved, understudied and uncured. Animal models for the study of CRC-induced cachexia, in particular models containing LM, are sparse; therefore, we aimed to characterize two new models of CRC cachexia. Male NSG mice were injected subcutaneously (HCT116) or intrasplenically (mHCT116) with human HCT116 CRC tumor cells to disseminate LM, whereas experimental controls received saline (n=5-8/group). Tumor growth was accompanied by loss of skeletal muscle mass (HCT116: −20%; mHCT116: −31%; quadriceps muscle) and strength (HCT116: −20%; mHCT116: −27%), with worsened loss of skeletal muscle mass in mHCT116 compared with HCT116 (gastrocnemius: −19%; tibialis anterior: −22%; quadriceps: −21%). Molecular analyses revealed elevated protein ubiquitination in HCT116, whereas mHCT116 also displayed elevated Murf1 and atrogin-1 expression, along with reduced mitochondrial proteins PGC1α, OPA1, mitofusin 2 and cytochrome C. Further, elevated IL6 levels were found in the blood of mHCT116 hosts, which was associated with higher phosphorylation of STAT3 in skeletal muscle. To clarify whether STAT3 was a main player in muscle wasting in this model, HCT116 cells were co-cultured with C2C12 myotubes. Marked myotube atrophy (-53%) was observed, along with elevated phospho-STAT3 levels (+149%). Conversely, inhibition of STAT3 signaling by means of a JAK/STAT3 inhibitor was sufficient to rescue myotube atrophy induced by HCT116 cells (+55%). Overall, our results indicate that the formation of LM exacerbates cachectic phenotype and associated skeletal muscle molecular alterations in HCT116 tumor hosts.